Striking evidence? Demand persistence for inter-city buses from German railway strikes - Matthias Beestermöller (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2017)
This paper investigates the effect of the largest rail strikes in German history in 2014-2015 on long-distance buses - a newly liberalized market. Using a novel dataset of detailed bus ticket sales and rail cancellations, I find that the primary channel that drives ticket sales during the strike is whether the absolute bus travel time was sufficiently short. In a difference-indifferences framework, I exploit this variation to identify any demand persistence. Although the common trend assumption does not seem to be completely tenable in the given context, my results point to a persistent effect on the ticket sales for inter-city buses on the affected routes.
urn:nbn:de:bvb:19-epub-31768-4
Keywords: L92; R41; C81; 330; Transportation; Long-Run Demand Effects; Intermodal Substitution; Strike